1997
DOI: 10.1093/infdis/175.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and Antibody-Dependent Cellular Cytotoxicity Responses against the BamHI A Rightward Open-Reading Frame-1 Protein of Epstein-Barr Virus (EBV) in EBV-Associated Disorders

Abstract: Antibody-dependent cellular cytotoxicity (ADCC) is an important antiviral effector mechanism. ADCC to the protein encoded by the Epstein-Barr virus (EBV) BamHI A rightward open-reading frame-1 (BARF1) was studied by transducing Raji-tk- cells with the BARF1 gene using a retroviral expression vector. The transduced Raji cells expressed BARF1 on the cell surface, as determined by flow cytometry. Sera from chronic and acute infectious mononucleosis and nasopharyngeal carcinoma patients were found to contain antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Since antibody dependent cell cytotoxicity (ADCC) response could be detected in the presence of NPC sera on a BARF1-transfected NKresistant Raji cell line from our laboratory (Tanner et al, 1997), it would be interesting, in consideration of BARF1 expression in NPC biopsies, to know whether BARF1-expressing epithelial cells could also be targets for speci®c killer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since antibody dependent cell cytotoxicity (ADCC) response could be detected in the presence of NPC sera on a BARF1-transfected NKresistant Raji cell line from our laboratory (Tanner et al, 1997), it would be interesting, in consideration of BARF1 expression in NPC biopsies, to know whether BARF1-expressing epithelial cells could also be targets for speci®c killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning immuno¯uorescence, Figure 5 shows the results obtained on acetone ®xed slides from primary Patas cells and BARF1 transfectants treated either with the NPC serum Tu 115 (A and B), or with rabbit polyclonal antibodies raised to a synthetic peptide from the BARF1 ORF (C and D). Tu 115 has long been used for the detection of the BARF1 protein by immuno¯uorescence, as well as immunoprecipitation and immunoblot (Zhang et al, 1988;Wei and Ooka, 1989;and de Turenne-Tessier et al, submitted), and our anti-peptide rabbit serum has been shown to recognize the BARF1 protein at the surface of transfected lymphoblastoid cells (Tanner et al, 1997). While no immuno¯uorescence was observed with either human EBV-negative or rabbit preimmune sera (not shown), both the Tu 115 serum and the anit-peptide rabbit antibodies gave a cytoplasmic and membrane response with BARF1 transfectants (B and D) but not with primary Patas cells (A and C).…”
Section: Presence and Expression Of The Barf1 Sequence In Transfectantsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, BARF1 has been shown to serve as a target for antibody-dependent cellular cytotoxicity (ADCC) (Tanner et al, 1997). These observations suggest that the biological activity of BARF1 might concern immunomodulation besides oncogenicity.…”
Section: Introductionmentioning
confidence: 99%